2011
DOI: 10.1002/spe.1039
|View full text |Cite
|
Sign up to set email alerts
|

Experience with fault injection experiments for FMEA

Abstract: Failure Modes and Effects Analysis (FMEA) is a widely used system and software safety analysis technique that systematically identifies failure modes of system components and explores whether these failure modes might lead to potential hazards. In practice, FMEA is typically a labor‐intensive team‐based exercise, with little tool support. This article presents our experience with automating parts of the FMEA process, using a model checker to automate the search for system‐level consequences of component failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…Apart from the aforementioned shortcomings, the following limitations have been also identified by other authors [8,9,17,18]:…”
Section: Limitationsmentioning
confidence: 99%
“…Apart from the aforementioned shortcomings, the following limitations have been also identified by other authors [8,9,17,18]:…”
Section: Limitationsmentioning
confidence: 99%
“…Model-based SW-FMEA in this sense has been proposed recently [14,9]. Executable models enable the analysis of software behavior either by simulation, where potential execution traces are sampled and analyzed, or by exhaustive and systematic analysis of the whole state space.…”
Section: Software Fmeamentioning
confidence: 99%
“…The work in [9] is based on the simulation of executable software models with model-level fault injection. An earlier approach, similar to the one presented in this paper, uses model checking (a technique for systematic formal analysis) to detect the violation of the system-level specification in case active faults are present [14]. Similar techniques are used for the analysis of fault tolerance mechanisms.…”
Section: Software Fmeamentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of slicing is to reduce (prior to model checking) a large model to a bisimilar slice which can be model checked instead of the original model, to combat the state explosion problem inherent to model checking. Based on our past experience in the domain of safety analysis, e.g., [8,9,10] we found that there are many cases in which the temporal logic formula of interest includes the next-step operator, and hence these formulas must be preserved by the slice. In the second part of this paper we introduce the resulting new slicing approach for the Behavior Tree modelling notation which is a graphical formal notation that supports the user in capturing informal requirements [11,12].…”
Section: Introductionmentioning
confidence: 99%